Road Traffic Accidents in Prithvi Highway, Nepal: A Spatiotemporal Analysis - Bhatta, Youb Raj; Rijal, Kedar; Pant, Ramesh Raj; Khadka, Rabin; Bhatta, Shashank; Negi, Crimsan S; Pali, Puja; Gyawali, Rajeev (Journal of Engineering Technology and Planning, 2025)
Road transport networks are vital catalysts for socioeconomic development and connectivity; their rapid expansion is inextricably linked to the critical global challenge of Road Traffic Accidents (RTAs). RTAs constitute a persistent public safety challenge in Nepal, with the Prithvi Highway recognized as one of the country’s most hazardous transport corridors due to its complex terrain, geometric deficiencies, and escalating traffic demand. This study employs a GIS-based spatiotemporal analytical framework to examine crash distribution along the highway from 2019 to 2025 AD. Secondary crash records were systematically cleaned, geocoded, and evaluated using Kernel Density Estimation (KDE) to detect spatial clustering, while Global Moran’s I statistics were applied to assess spatial autocorrelation across crash attributes. The temporal assessment revealed substantial annual variability, including a distinct peak in 2021 AD, alongside a consistent predominance of daytime crashes across all districts, reflecting higher exposure during active traffic periods. Spatial analysis identified persistent and high-intensity hotspots in the Kathmandu–Thankot, Khairghari–Malekhu, Kurintar–Mugling, and Aabukhaireni–Damauli sections, confirming strong clustering of crash events. Moran’s, I result indicated statistically significant spatial dependence for total crashes, injuries, and age-group involvement, whereas fatalities exhibited a random spatial pattern, suggesting the influence of situational rather than locational determinants. Contributing factors were closely associated with geometric constraints, including narrow carriageways, sharp curves, inadequate super-elevation, and restricted sight distances, compounded by environmental stressors such as monsoon-induced landslides, surface runoff, and winter fog. The findings underscore the necessity of targeted, corridor-specific interventions involving geometric upgrades, slope stabilization, enhanced drainage, seasonal risk mitigation, and data-driven enforcement. This study provides a robust scientific basis for developing precise and sustainable road safety strategies along one of Nepal’s most critical national highways.